A novel shape memory alloy damping inerter for vibration mitigation. (1st October 2019) - Jia, Yingqi; Li, Lingzhi; Wang, Chao; Lu, Zhoudao; Zhang, Ruifu
Abstract: Various shape memory alloy (SMA) dampers have been developed to reduce structural vibration responses. However, the application of SMA dampers has been restricted by the high material costs of SMAs. Therefore, this study developed and tested an innovative SMA damping inerter (SDI) in which an SMA element and an inerter element were arranged in parallel and deployed in series with a supporting spring element. A single-degree-of-freedom structure with an SDI was employed to analyze the effect of vibration mitigation. A theoretical analysis was conducted via an equivalent linearization method, and parameter studies were then used to evaluate the performance of the SDI-fitted structure from perspectives of structural displacement, acceleration, and energy dissipation as well as the most efficient frequency tuning bandwidth. The performances of the SDI and a conventional SMA damper were compared by using a time-domain analysis with recorded and simulated ground motions, revealing clearly superior results for the SDI with respect to structural response mitigation, and seismic energy dissipation. The system proposed here took advantage of the full potential of combining SMA and inerter elements, making the SDI a robust system for mitigating structural vibration with more economical SMA material costs.